"He's Not Good at Sensing That Look That Says, I'm Drowning Here!" Academic Mothers' Perceptions of Spousal Support. Issue 3 (2nd April 2020) - Dickson, Martina
Abstract: Research consistently shows that, regardless of increased parental involvement in child-rearing over the last few decades, the 'lion's share' of childcare and housework is still undertaken by women rather than men. Academia is known to have no fixed working hours as such. As a result, the pressure on academic mothers tends to be inflated, and this has repercussions on women's promotional paths, publishing outcomes and general professional and personal well-being. The positive effect of working women having spousal support is well documented in many employment areas. This paper looks at perceived spousal support which academic mothers, living and working in the United Arab Emirates (UAE), report. While some of the women did report their spouses to be supportive, this was often theoretical rather than practical. The ways in which this spousal support situation has affected the academic mothers' lives is discussed.